PELATIHAN PEMBUATAN POUCH ANYAMAN DENGAN TEKNIK DECOUPAGE BAGI GURU SLBN 1 YOGYAKARTA - Laila Nurul Himmah; Mahanani, Chytra; Sepsilia Elvera, Resi; Eka Putri, Gina (Universitas Negeri Jakarta, 2023)
ABSTRACT. Educators have a very important role in the process of determining the potential development of children with special needs according to the conditions and needs of referrals of children with special needs, extraordinary school teachers (SLB) are professional teachers in the field of knowledge of children with special needs. This is inseparable from the creativity of teachers to always provide an innovation, for example by utilizing a pandan woven pouch as a product with a decoupage technique so that it has a high selling value. The purpose of this activity is to increase creativity in making woven pouch decorations that have a selling value, provide knowledge of making woven pouches with decoupage techniques and instill the entrepreneurial spirit of SLB N 1 Yogyakarta teachers so that they are able to produce products that are in great demand by consumers, provide knowledge about the fashion business including calculation of selling prices, and marketing strategies. This activity is carried out by the method of lectures, demonstrations, training and practice. Based on the results of product manufacturing during practice, participants were very enthusiastic about practicing the material provided. The results of the participants' practice also varied, namely each participant made different motif creations by combining various kinds of tissue decoupage motifs. Participants Increase knowledge of decoupage techniques through a process of creativity and innovation in order to increase income and be able to disseminate to students and students of SLB. Through this training, teachers have the skills to improve the quality of human resources which can be used as a provision for opening a business while creating jobs. Keywords: Training, Creativity, Economic Value, Decoupage, Woven